2003
DOI: 10.1093/jnci/95.5.362
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for Elderly Patients With Advanced Non-Small-Cell Lung Cancer: The Multicenter Italian Lung Cancer in the Elderly Study (MILES) Phase III Randomized Trial

Abstract: The combination of vinorelbine plus gemcitabine is not more effective than single-agent vinorelbine or gemcitabine in the treatment of elderly patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
482
8
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 754 publications
(519 citation statements)
references
References 32 publications
10
482
8
16
Order By: Relevance
“…In contrast to the present study, the Multicenter Italian Lung cancer in Elderly Study (MILES) showed no survival benefit from gemcitabine plus vinorelbine (MTS, 30 weeks) vs either single agent (MST, 28 and 36 weeks, respectively) (Gridelli et al, 2003). However, 20% of patients entered in the MILES trial were affected by three, and 25% of patients by four or more associated diseases.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast to the present study, the Multicenter Italian Lung cancer in Elderly Study (MILES) showed no survival benefit from gemcitabine plus vinorelbine (MTS, 30 weeks) vs either single agent (MST, 28 and 36 weeks, respectively) (Gridelli et al, 2003). However, 20% of patients entered in the MILES trial were affected by three, and 25% of patients by four or more associated diseases.…”
Section: Discussioncontrasting
confidence: 93%
“…The enrolment started in May 1999, and we anticipated to complete the case accrual in about 4 years. However, in March 2003 we decided to close the recruitment, in consideration of the slower than anticipated accrual, and on the basis of some ethical concern raised by a recently published trial in elderly patients, in which no survival benefit derived for the combination of gemcitabine plus vinorelbine over gemcitabine alone (Gridelli et al, 2003). Participating investigators were required to perform an ad hoc analysis of survival for patients enrolled until that date, allowing for a 6-month minimum follow-up after the last patient had been recruited.…”
Section: Statistical Analysis and Sample Sizementioning
confidence: 99%
“…Therefore, a single agent such as vinorelbine, whose effect on prolonging survival in advanced NSCLC with elderly has been demonstrated in comparison to the best supportive care (Anonymous, 1999), is sometimes selected to treat such patients in practice. In addition, the combination of vinorelbine plus gemcitabine has been reported to be not more effective than single-agent vinorelbine or gemcitabine in the treatment of elderly patients with advanced NSCLC (Gridelli et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11 Recently, two randomized Phase III trials evaluated the efficacy of was terminated early (JCOG0803/WJOG4307L). 13 In this trial, the combination regimen was again more toxic.…”
Section: Discussionmentioning
confidence: 99%
“…6 Since then, vinorelbine monotherapy has become one of the most important chemotherapy regimens for elderly patients. 5,7 Carboplatin is a platinum derivative with less renal toxicity and causes less nausea and vomiting than cisplatin. 8 We therefore considered that vinorelbine and carboplatin could be an effective combination for elderly patients with previously untreated NSCLC and planned Phase I and II trials of this combination regimen.…”
Section: Introductionmentioning
confidence: 99%